Persuasive discourse in selected ceremonial speeches by Mother Teresa - Sharif, Azadeh (2015)
Critical Discourse Analysis (CDA), as a multidisciplinary approach, views discourse as a form of social action, which does ideological work in the representation of social reality and the construction of identities. In analyzing language as discourse, together with other semiotic modalities, CDA seeks to explain how functions, topics,strategies, and other properties of discourse play a role in manifesting the public as well as private intentions of the producer of discourse. The present study investigated the persuasive discourse of Mother Teresa in selected ceremonial speeches via an examination of textual patterns, generic move structures, social themes and topics, as well as discursive strategies and related rhetorical devices. The textual data of the study consisted of three selected speeches of Mother Teresa:(1) the Nobel Peace Prize acceptance speech (1979), (2) the Class Day address (1982), and (3) the National Prayer Breakfast address (1994). The speech texts were examined: (1) to identify textual patterns and construction of MT’s speeches selected for the study; (2) to describe the main generic move structures and the related steps used by Mother Teresa; (3) to determine the recurrent themes and topics; (4) to identify the discursive strategies and the argumentative schemes; (5) to analyze the linguistic means and devices employed; and (6) to reveal the ideological stances of Mother Teresa that appear to underlie her discourse. The results of the identification of the textual patterns and construction of MT’s speeches revealed that MT’s speeches in general followed the pattern of Situation- Problem-Response-Evaluation. However, it was found that Responses/solutions mainly constructed MT’s discourse. The analysis of the means of persuasion employed in giving Responses/solutions by MT in the speeches demonstrated that emotional appeals of repetition and motive words were the chief sources of persuasion. Appeal to logic by means of narration was found as the most recurrent source of persuasion after emotional appeals. Finally, the results also indicated that appeal to authority and the use of inclusive language were other repeated means of persuasion through character used by MT in offering Responses/solution in the speeches. The results of the identification of the generic move structures of the three selected speeches of Mother Teresa showed that the predominant generic moves, and in particular, their constituent steps which are potentially persuasive in nature, included establishing commonalities with the audience, urging and inviting the audience to take proactive actions, appealing to religious authorities, narrating anecdotes from the Holy Book and the stories of her personal experiences, stating the humanitarian activities of the Missionaries of Charity in a positive light, encouraging collaboration, presenting social problems, stating her general and religious beliefs,and providing statistics. Topics such as love, Jesus, and children along with the related themes of sacrifice in love, passions/sacrifices of the Christ, and supporting children constituted the core concerns of Mother Teresa’s selected speeches. Discursive strategies such as nomination, predication, and argumentation were utilized to advocate the moves, steps, topics, and themes. The discursive analysis indicated that nomination strategy was mainly used to shape the beliefs, feelings, and views of the audience by establishing credibility; emphasizing the messages and acts of religious authorities; promoting peace,advocating giving love, encouraging adoption, and calling attention to human values. Moreover, it was found that by means of the predication strategy, there was a tendency to persuade the audience to gain particular ideological views such as the omnipresence of Christ, as well as being pro-children and the poor. In addition, the use of the argumentation strategy mainly served to motivate the audiences to give love sacrificially and have trust in God’s love. Finally, the analysis indicated that Mother Teresa’s main ideological stances of antiabortion,pro-adoption and natural family planning, Jesus in the guise of the poor/omnipresence of Jesus, and the necessity of doing sacrifice in love were discursively realized via salient topics and themes, and particularly through discursive strategies that were linguistically identified via a transitivity analysis. The findings shed more light on our understanding of the nature of persuasion as a social act in terms of its discursive construction and representation in ceremonial speeches by a well-known social actor such as Mother Teresa.